Reducing The Time of Picking up Orders A Case Study of Construction Materials Warehouse - Anurattananon, Chanpen; Klomjit, Prachuab; Saelem, Sittichai; Kujirapan, Kanyaphuk; Charoennoppakit, Tibet; Yahatta, Papatsara (Thai Industrial Engineering Network Journal, 2019)
The purpose of this project is to improve and reduce the time to process the products according to the goods inside the warehouse of building materials. The study and analysis of the suitability of the sort used 3 different alignment with sales. sorting by the way bill,. and sorting of mixed method in order to provide operational guidance, effective and worth the cost. This research Started by conducting research and analysis of the current condition of the building materials warehouse Thananan Hardware Co.,Ltd. Nakhon Pathom. The research group led by a zone warehouse roof tiles which have 2 types of roof tiles and roof coverings because in this zone is the longest process flow and product placement was mingled and found it difficult to pick up. The location was unknown and it took time to find the goods produced on the inside. ABC Analysis was used as tool for classification and importance of this zone. There was a study guide divided into three cases, that were alignment with sales. sorting by the way bill, and sorting of mixed method in order to find a way to keep the best and most effective. The result was found that the positioning of the product as a warehouse to store 1 was based on sales. Picking times was reduced in both type 2 29.39% and 4.39%, respectively, compared to the original position. And reduced cost of workers and fuel 25% and 19%, respectively, which resulted from the trial of the placement of products on the warehouse with minimum cost and time.